Locality Domains in Syntax: Evidence from Sentence Processing. (7th May 2020) - Keine, Stefan
Abstract: One of the main discoveries of generative syntax is that long‐distance extraction proceeds in a successive‐cyclic manner, in that these dependencies are comprised of a sequence of local extraction steps. This article provides support for this general picture by presenting novel parsing evidence for intermediate landing sites created by successive‐cyclic movement, and it uses this parsing evidence to investigate the distribution of intermediate gaps. The central findings of this article are that (i) there is evidence that successive‐cyclic movement targets the edge of CPs and that (ii) there is no comparable evidence for an intermediate landing site at vP edges. These findings are fully consistent with the classical view of successive cyclicity, according to which only finite‐clause edges host intermediate landing sites. In the context of phase theory, these results receive a straightforward explanation if CPs are phases but vPs are not. The processing evidence presented here thus provides a novel diagnostic for the distribution of phases and new evidence for their active role in online sentence processing.